Tibetan houses : vernacular architecture of the Himalayas and environs - Herrle, Peter; Alexander, Andre; Wozniak, Anna (Basel ; Boston : Birkhauser, 2017)
'The region of the Himalayas and the adjoining Tibetan plateau is known for its unique and characteristic vernacular architecture and housing culture which is slowly but surely disappearing.The book analyses 19 traditional houses in the region that respond in diverse ways to the specifics of their location and local climate, and presents a comparative study of the construction elements using photographs and hand-drawn construction details'--
Includes bibliographical references (pages 294-297).
Keywords: Architecture, Domestic -- Tibet Region -- Designs and plans; Architecture, Domestic -- Himalaya Mountains Region -- Designs and plans; Vernacular architecture -- Tibet Region -- Designs and plans; Vernacular architecture -- Himalaya Mountains Region -- Designs and plans